2012
DOI: 10.1097/wnr.0b013e32834ebf44
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of primary auditory cortex in autistic spectrum disorder with auditory hypersensitivity

Abstract: The aim of this study was to investigate the differential responses of the primary auditory cortex to auditory stimuli in autistic spectrum disorder with or without auditory hypersensitivity. Auditory-evoked field values were obtained from 18 boys (nine with and nine without auditory hypersensitivity) with autistic spectrum disorder and 12 age-matched controls. Autistic disorder with hypersensitivity showed significantly more delayed M50/M100 peak latencies than autistic disorder without hypersensitivity or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 15 publications
2
52
0
1
Order By: Relevance
“…Reports have indicated that the ASD population exhibits elevated rates of brain stem or peripheral hearing dysfunction [13][14][15][16][17][18][19][20] and abnormalities in AEF components (i.e., cortical dysfunction) [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25]. Intriguingly, research has indicated that individuals with ASD may present with peripheral auditory asymmetry [13], which may distort the cortical bilateral synchronization of AEF components in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reports have indicated that the ASD population exhibits elevated rates of brain stem or peripheral hearing dysfunction [13][14][15][16][17][18][19][20] and abnormalities in AEF components (i.e., cortical dysfunction) [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25]. Intriguingly, research has indicated that individuals with ASD may present with peripheral auditory asymmetry [13], which may distort the cortical bilateral synchronization of AEF components in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Altered auditory processing systems in children with ASD have been studied as neurological correlates of some phenotypes in ASD, such as inhibited language acquisition [1][2][3][4][5][6][7][8] and auditory hypersensitivity [9][10][11], and previous studies that have focused on auditory responses of the brain have also demonstrated altered cerebral laterality [2,5,6] and regional connectivity [12] in children with ASD. These studies have indicated alterations in cortical auditory processes in ASD [1,2,4,5,9,10], whereas increased rates of brain stem or peripheral hearing dysfunction have also been reported in the ASD population [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these electrophysiological studies showed auditory processing differences between autistic and control patients, the cause of auditory hypersensitivity remains unknown. Recently, it has been thought to be associated with decreased inhibitory processing, possibly resulting from the dysfunction of inhibitory interneurons or an abnormal sensory gating system (4,9). Its relation to drugs has not been well documented to date.…”
Section: Introductionmentioning
confidence: 99%